Extraction optimization, characterization and evaluation of antioxidant and nutraceutical properties of date palm (Phoenix dactylifera l., variety Ajwa) kernel - Hosni, Suzziyana (2020)
Several studies have advocated that date palm Phoenix dactylifera L. kernels, generally regarded as unwanted agricultural waste, is of high potential as a nutraceutical product. The present study was conducted on variety Ajwa to investigate kernels’ potential by determining the optimum conditions for antioxidant extraction thereby increasing efficiency in subsequent processes. Response surface methodology (RSM) was employed using four independent variables viz. roasting temperature (180-220°C), roasting time (30-120 minutes), extraction temperature (80-160°C), and extraction time (30-120 minutes). The results demonstrated that roasting at 200°C for 74 minutes and aqueous extraction at 123°C for 79 minutes had effectively resulted in optimum 2,2- diphenyl-1-picrylhydrazyl (DPPH) (93.03 % inhibition), total flavonoid content (TFC) (14.341mg QE/100mL), total phenolic content (TPC) (987.4mg GAE/100mL) and ferric reducing antioxidant power (FRAP) (90.63mM Fe2+/100mL). The coefficients of determination (R2 values) for the same four parameters were recorded at 0.962, 0.935, 0.946, and 0.924 respectively. The study put forward efficient process parameters with the objective of increasing production efficiency while exploiting the potentialities of date palm kernels as a nutraceutical product. Proximate analyses were done by methods described by Association of Official Analytical Chemists (AOAC) and mineral nutrients were assessed using inductively coupled plasma mass spectrometry (ICP-MS). Proximate analysis further showed that the kernels contained 65.0±2.6% crude fibre, 6.0±0.20% crude protein, 5.00±0.20% moisture, 8.05±0.40% crude fat and 1.20±0.05% ash. Among the mineral nutrients, potassium recorded maximum amount at 376.39±12.3mg/100g followed by phosphorus 126.46±5.04mg/100g, magnesium 78.16±2.14mg/100g, calcium 19.24±1.02mg/100g and sodium 14.91±0.58mg/100g of kernels. The high chromatogram peak of the phenolic compound that available inside kernels was confirmed using ultra-highperformance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF / MS) while evaluation for their potentials in α- glucosidase and cancer inhibition activity was conducted using standard in vitro inhibition assay. The outcome showed that date palm kernels had a potent inhibitory activity of α-glucosidase up to 96.62% at a concentration of 34.7533μg/mL and inhibited cancer cells to 57.76 and 53.47% in HT-29 and CRL1739 cells, respectively, at a concentration of 500μg/mL. In agreement with previous studies on nutritional benefits of date kernels, the Ajwa date is potentially a promising candidate for pharmaceutical applications or functional food impacting healthcare system in numerous positive ways based on their bioactive constituents and antioxidant profiles.